Jejak Tafsir Ulama Arab Asal Nusantara - Ni'matul Maula; Norma Azmi Farida (INC- Islam Nusantara Center, 2022)
This paper identifies the study of the book of Tafsir al-Khatib al-Makki, a book written by Arab scholars of Minangkabau descent, namely Sheikh Abdul Hamid bin Ahmad Khatib al-Minangkabawi. In its history, mufassir lived, settled, became a cleric to a diplomat and died outside Indonesia, precisely in Arabia. The profile of Sang Mufassir as the son of a famous Indonesian cleric became an attraction in itself. Moreover, the name of the interpretation that attaches to the father's name, namely 'Al-Khatib' is often misunderstood as the work of Sheikh Ahmad Khatib Al-Minangkabawi, even though it is the work of his son. Its unrevealed traces are an attempt to compile a mosaic of interpretations from the archipelago. This article includes qualitative research that captures systematics, writing methods, and writing patterns. The identification carried out is the first step in reviewing a work of interpretation with the following analysis results, this book consists of 4 volumes covering 13 juz in Arabic and is compiled in the Ottoman mushaf format. Judging from the source, the book is categorized as an interpretation of bi al-ra'yi. Meanwhile, based on the method, Sheikh Abdul Hamid al-Khatib used the tahlili method. Meanwhile, the pattern used in this interpretation is adabi ijtima'i. Karya tulis ini mengidentifikasi kajian kitab Tafsir al-Khatib al-Makki, kitab yang ditulis oleh ulama Arab yang berasal dari keturunan Minangkabau yaitu Syekh Abdul Hamid bin Ahmad Khatib al-Minangkabawi. Dalam sejarahnya, mufassir tinggal, menetap, menjadi ulama hingga diplomat dan wafat di luar Indonesia, tepatnya di Arab. Profil Sang Mufassir sebagai putra ulama kesohor Nusantara menjadi daya tarik sendiri. Terlebih, nama tafsir yang menisbatkan kepada nama sang ayah yakni ‘Al-Khatib’ acap kali disalahpahami sebagai karya Syekh Ahmad Khatib Al-Minangkabawi, padahal karya putranya. Jejaknya yang belum banyak diungkap merupakan upaya untuk menyusun mozaik khazanah tafsir asal Nusantara. Artikel ini termasuk penelitian kualitatif yang memotret sistematika, metode penulisan, hingga corak penulisannya. Identifikasi yang dilakukan merupakan langkah awal dalam mengkaji suatu karya tafsir dengan hasil analisa sebagai berikut, kitab ini terdiri dari 4 jilid yang mencakup 13 juz berbahasa Arab dan disusun dengan format mushaf Utsmani. Ditinjau dari sumbernya, kitab tersebut dikategorikan sebagai tafsir bi al-ra’yi. Sedangkan berdasarkan metode, Syekh Abdul Hamid al-Khatib menggunakan metode tahlili. Sementara corak yang digunakan dalam tafsir ini yaitu adabi ijtima’i.